Fanatisme dalam Praktik Pendidikan Islam - Muhammad Misbah; Jubaedah Jubaedah (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2021)
This paper examines the problem of fanaticism in Islamic education in Indonesia. As a plural country with its diversity, a high sense of tolerance is needed in Indonesia. This research is a qualitative research with library research. Documentation methods were used in this study to collect data from various literature, such as books, journals, and other electronic sources. The data is analyzed using content analysis method, whereas in the conclusions is drawn using an inductive mindset. The results of the study concluded that the paradigm of Islamic education should be done through multicultural inclusive education and prophetic education. Islamic Education (PAI) teachers in this regard have an important role in instilling a harmonious sense of religion. Inclusive multicultural education is expected to foster a sense of belonging and togetherness, dissociated from primordial barriers by emphasizing plurality-based religious education.